My name is Gabriela : the life of Gabriela Mistral = Me llamo Gabriela : la vida de Gabriela Mistral - Brown, Monica, 1969- (Luna Rising, 2005)
Gabriela Mistral loved words, sounds and stories. Born in Chile, she would grow to become the first Nobel Prize-winning Latina woman in the world. As a poet and a teacher, she inspired children across many countries to let their voices be heard.